Logos without Rhetoric : The Arts of Language before Plato - Schiappa, Edward, 1954-; Reames, Robin (Book collections on Project MUSE., 2017)
"How did rhetoric begin and what was it before it was called "rhetoric"? Must art have a name to be considered art? What is the difference between eloquence and rhetoric? And what were the differences, if any, among poets, philosophers, sophists, and rhetoricians before Plato emphasized--or perhaps invented--their differences? In Logos without Rhetoric: The Arts of Language before Plato, Robin Reames attempts to intervene in these and other questions by examining the status of rhetorical theory in texts that predate Plato's coining of the term rhetoric (c. 380 B.C.E.). From Homer and Hesiod to Parmenides and Heraclitus to Gorgias, Theodorus, and Isocrates, the case studies contained here examine the status of the discipline of rhetoric prior to and therefore in the absence of the influence of Plato and Aristotle's full-fledged development of rhetorical theory in the fourth century B.C.E."--